Permanent Deformation of Hot Mix Asphalt (HMA) using Dynamic Modulus Simple Performance Test - Ekarizan, Shaffie; Ahmad Kamil, Arshad; Putra Jaya, Ramadhansyah; Wardati, hashim; Mohd Amin, Shafii (Blue Eyes Intelligence Engineering & Sciences Publication, 2019)
Premature pavement breakdown can be caused by permanent deformation that can contribute to lower riding comfort for road users and an increase in maintenance costs. Dynamic modulus Simple Performance Test (SPT) test are considered to be significant in describing the permanent deformation of hot mix asphalt. In this study, Marshall method of mix design were used in order to prepare four asphalt mixtures comprising different content of Nanopolyacrylate (NP) polymer (0%NP, 2%NP, 4%NP and 6%NP). This study was aimed to evaluate the influence of the NP modified mixture on the permanent deformation. The Performance Grade PG64-22 was obtained by mixing the conventional bitumen (PG64-22) with nanopolyacrylate. Dynamic Shear Rheometer (DSR) at different aging condition were conducted in order to characterise the bitumen performance. While, the Simple Performance Test (SPT) was used to characterize rutting and fatigue on Marshall HMA mixes. Results from the study presented that, NP modified bitumen has a significant impact on the dynamic and rutting resistance. The addition of nanopolyacrylate significantly enhances the rheological properties of asphalt bitumen. The results revealed that 4%NP has high potential to improve rutting and fatigue resistance